The Necessity of Atheism - Rodriguez, Agustin Martin G (Archīum Ateneo, 2020)
In this lecture, Doc Guss discusses atheism from a philosophical perspective: tracing its origins and explaining how humans came to embrace it as a response to the absurdity of their own existence (don't worry, it isn't as bad as it sounds). He then poses the question—is the 'atheist' human truly flourishing? Speaker: Agustin Martin G. Rodriguez is a professor of the Department of Philosophy. He also served as chair of the Philosophy Department from 2009-2015. He obtained his Master of Arts in Philosophy and Doctorate of Philosophy in Philosophy from Ateneo de Manila University. His research work has been mostly on the rationality of the marginalized, specifically on issues like human rights, democratic governance and grassroots empowerment, and on such thinkers as Scheler, Habermas, and Derrida.